IDEAS ON MORAL EDUCATION IN THE WORKS OF IMAM BUKHARY - Shabdullayeva Nazokat; Tajiddinova Laylokhan (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
In the article, the global significance of Imam Bukhari’s spiritual heritage and the moral and educational significance of the works of scholars in the formation of positive qualities in the education of young people are studied.